Teoria geral do processo tributário - Pria, Rodrigo Dalla (2010)
This paper aims to delimitate the legal-normative range fitting to the tax procedural system in order to investigate the particular manner in which the procedural institutes are applied to the so called tax impleads or conflicting legal-tax relations. After defining the legal-philosophical and theoretical-legal premises that will support our dogmatic investigations, the concept of Tax Procedural Law is defined, as well as its repercussion on the three fundamental categories of the General Procedural Theory: the lawsuit the proceeding and the jurisdiction